Enantioselective in vitro metabolism of the fungicide penconazole by human liver microsomes and in vitro–in vivo extrapolation of hepatic clearance - Barbetta, Maike Felipe Santos; Brambilla, Tamires Helena Barretta; Perovani, Icaro Salgado; Duarte, Leandro Oka; Baviera, Giovanni Stoppa; Moraes de Oliveira, Anderson Rodrigo [UNESP] (Elsevier, 2025)
Contamination by chiral compounds may cause enantioselective toxicity and bioaccumulation. For chiral pesticides like penconazole (PEN), while using a mixture containing equal amounts of enantiomers is cost-effective, chiral effects may impact both targeted and non-targeted organisms. Enantioselective toxicity has been observed during PEN exposure to albino rats and various cell types, as well as differences in fungicidal activity. However, its effects in humans remain unclear, despite the known impacts of some triazole fungicides. The present work aimed to evaluate the in vitro metabolism of PEN using human liver microsomes, employing both the racemic mixture and isolated enantiomers to determine the half-life (t1/2), as well as the toxicokinetic parameters hepatic clearance (CLH) and extraction rate (EH) obtained after in vitro extrapolation. Enzyme phenotyping was also carried out employing the most relevant cytochrome P450 isoforms in humans. PEN exhibited a low metabolism rate, with t1/2 values ranging from 86 to 213 min, CLH values from 1.00 to 1.92 mL/min/kg and EH values from 5.0 % to 9.6 %, considering the first-pass effect in the liver and only phase I reactions. CYP3A4 was the major enzyme contributor to PEN metabolism, with little participation of CYP2C9 (R-(+)-PEN), CYP2C19 (S-(-)-PEN) and CYP3A5 (for both). Moreover, R-(+)-PEN was metabolized faster than S-(-)-PEN when the racemic mixture was employed, but similar values were obtained with the isolated enantiomers. These findings suggest enantioselective effects in the xenobiotic interaction in vivo, and a longer exposition to S-(-)-PEN.